Islam and Me Narrating a Diaspora. - Fazel, Shirin Ramzanali; Brioni, Simone; Burdett, Charles (Chicago : Rutgers University Press, 2023)
"Islam and Me is a meditation on our multireligious, multicultural, and multilingual reality. It is the result of a personal and collaborative exploration of the necessity to rethink national culture and identity in a more diverse, inclusive, and anti-racist way. Looking at school textbooks, newspapers, TV programs, and sharing her own personal experience, Shirin Ramzanali Fazel invites us to change the way Muslim immigrants, and especially Muslim women, are narrated in scholarly research and news reports. Most importantly, Shirin urges us to consider minorities not just as "topics" of cultural analysis, but as audiences and cultural agents. Following Shirin's invitation to question prevailing modes of representations of immigrants, the volume also includes a dialogue between the author and the editor, which discusses how collaboration can be a way to avoid reproducing a "colonial model" of knowledge production, in which the white male scholar takes as object of analysis the work of an African female writer"--
Notes -- References -- About the Contributors
Description based upon print version of record.
JSTOR
Keywords: Muslims -- Non-Islamic countries; Islamophobia; Cultural pluralism; Sex discrimination against women; Immigrants' writings -- History and criticism; Musulmans -- Pays non-musulmans.; Islamophobie; Diversité culturelle; Discrimination à l'égard des femmes; Écrits d'immigrants -- Histoire et critique; BIOGRAPHY & AUTOBIOGRAPHY / General; Cultural pluralism; Immigrants' writings; Islamophobia; Muslims; Sex discrimination against women; Non-Islamic countries; muslim, islam, religion, immigration, migration, emigration, expat, gender, culture, race, language, italy, discrimination, islamphobia, xenophobia, assimilation, politics, policy, women, diaspora, african, identity, belonging, italian, translation; Criticism, interpretation, etc